Students’ Satisfaction on Service Quality at Prithvi Narayan Multiple Campus of Tribhuvan University in Nepal - Adhikari, Santosh (Nepalese Journal of Public Affairs, 2023)
This study examines the students’ satisfaction on service quality of PNC. The main objective of the study is to analyze the major influencing factors of academic aspect of service quality, to measure the relationship of academic aspect of service quality with students’ satisfaction and to analyze the impact of academic aspects on students’ satisfaction on service quality. Philosophical foundation of this research is based on positivist research paradigm. Based on the philosophical foundation, this research has used descriptive and analytical research design. Using multi-phase sampling technique, this study reveals major influencing factor of academic aspect of service quality is quality of lecturers. The overall students’ satisfaction towards service quality provided by PNC is more than average. The learning environment of academic aspect has more influence in students’ satisfaction. Overall, there is high degree of positive correlation between academic aspect of service quality and students’ satisfaction. For academic aspect of service quality, only learning environment shows a statistically significant impact on students’ satisfaction. This study shows that academic aspects of service quality have positive impact on students’ satisfaction.